PERANAN KEPEMIMPINAN KEPALA DESA UNTUK MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PELAKSANAAN PEMBANGUNAN FISIK (STUDI DI DUSUN AHOLEANG DESA MEKKATTA KECAMATAN MALUNDA KABUPATEN MAJENE) - Yusuf Daud (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2017)
This study aims to determine the role of the leadership of the Village Head in increasing community participation in the implementation of physical development in Aholeang Hamlet, Mekkatta Village, Malunda District, Majene Regency. Data collection is done through observation data, interviews, and documentation studies. The results showed that the Mekkatta Village Chief of Malunda District Majene District had taken a very important role in increasing community participation in the implementation of physical development in Aholeang Hamlet, Mekkatta Village, Malunda District, Majene Regency.